Impact of pairing an augmented reality demonstration with online video lectures… Does it improve students’ performance? / Surendheran Kaliyaperumal ... [et al.] - Kaliyaperumal, Surendheran; Abd Wahab, Mohd Helmy; Sagayam, K. Martin; Ambar, Radzi; Mhd Poad, Hazwaj (Universiti Teknologi MARA, 2020)
Due to the increased shifts in recent technologies, the education sector has also started to reshape itself to face the future. Augmented Reality (AR) and Virtual Reality (VR) are among the few recent trends that drive this shift forward. This study was set to study the impact of pairing a video lecture course with an AR presentation. A class of multimedia students (N=33) from Vellore Institute of Technology, Vellore, India; underwent an experiment of watching a video lecture module and attending a quiz. The same class again went through a similar test where they had to watch video lectures, get to experience what they learned in Augmented Reality for 10minutes, and then appeared for the quiz. The paired t-test conducted on the two sets of scores obtained by the class indicates a statistically significant increase in the average final scores when AR experience is paired with the video lectures. The feedback from the students was also positive on the AR experience.